Enhancing Yield and Yield Components of Food Barley (Hordeum vulgare L.) Through Optimum Nitrogen and Phosphorus Levels in Eastern Amhara, Ethiopia - Sisay, Kassa (International Journal on Food, Agriculture and Natural Resources, 2025)
The correct application of plant nutrients depends on understanding the nutrient requirements of crops and the nutrient supply capacity of the soil. This study was carried out during the main cropping seasons of 2019 and 2020 to determine the economically optimum rates of nitrogen and phosphorus fertilizers for enhancing food barley production. The experiment was conducted using a factorial combination of three nitrogen rates (46, 69, and 92 kg N ha⁻¹) and three phosphorus rates (46, 69, and 92 kg P₂O₅ ha⁻¹) in a randomized complete block design with three replications. The plant height, biomass, and adjusted grain yield were collected and analysis of variance was conducted using SAS version 9.0. The results indicated that the applications of nitrogen and phosphorus containing fertilizers significantly enhanced the grain and biomass yield of food barley. The analyzed data clearly showed that yield and yield-related data of barley increased with increased nitrogen and phosphorus rates. The highest above-ground biomass yield (5466.2kgha-1) and the maximum grain yield (2884.6 Kg ha-1) were obtained with the application of 92 Kg ha-1 nitrogen and 92 Kg ha-1 P2O5, significantly outperforming all other treatments. However, the application of 92 kg of nitrogen and 69 kg of phosphorus kg ha-1 gave the highest economic benefit (53,592.3) with a marginal rate of return (1597.1%) resulting in higher net benefits than the other treatments. Therefore, the application of 92 kg N and 69 kg P2O5 kg ha-1 is recommended for food barley production in the study area and similar agro ecologies.